2018
DOI: 10.3201/eid2404.171783
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Enterovirus A71 Circulating in Africa

Abstract: We analyzed whole-genome sequences of 8 enterovirus A71 isolates (EV-A71). We confirm the circulation of genogroup C and the new genogroup E in West Africa. Our analysis demonstrates wide geographic circulation and describes genetic exchanges between EV-A71 and autochthonous EV-A that might contribute to the emergence of pathogenic lineages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 14 publications
(25 reference statements)
2
20
0
Order By: Relevance
“…The fact that severe complications associated with EV-A71 infections mostly occur in countries of the Asia-Pacific region is intriguing as EV-A71 appears to be widely circulating in other areas of the world. New genogroups have been recently described in India [ 31 ] and Africa [ 34 ], and also now in Pakistan, as we show here. It will be worth investigating further the differences in clinical severity induced by EV-A71 infections in different geographical regions.…”
Section: Discussionsupporting
confidence: 77%
“…The fact that severe complications associated with EV-A71 infections mostly occur in countries of the Asia-Pacific region is intriguing as EV-A71 appears to be widely circulating in other areas of the world. New genogroups have been recently described in India [ 31 ] and Africa [ 34 ], and also now in Pakistan, as we show here. It will be worth investigating further the differences in clinical severity induced by EV-A71 infections in different geographical regions.…”
Section: Discussionsupporting
confidence: 77%
“…Contigs were queried against the ViPR database 59 retrieved in march 2019 using DIAMOND 60 . In addition to contigs matching EVA-71 (7345 (0.02%) reads mapped to this virus), whose sequence was previously obtained 13 , two large contigs corresponded to HePVs sequences. Using the sequence from the top DIAMOND hits (ADA79690, ANJ01603) as reference, HePVs contigs were assembled into a full-length HePV scaffold with missing sections (gaps).…”
Section: Sample Collection and Virus Isolationmentioning
confidence: 87%
“…It has been successfully used to identify or characterize full-genomes of new HPeVs like a HPeV1 variant 35 , type 4 31 , types 5 and 6 32 , type 7 36 , type 16 26 , type 17 37 , types 18 and 19 38 or to detect HPeVs in clinical specimens 25,26,[39][40][41] . Thanks to NGS, we were able to detect a mixed infection of HPeV15 and EV-A71 when using this technique to characterize the full genome sequence of EV-A71 13 . Several studies have reported HPeVs in mixed infections.…”
Section: Discussionmentioning
confidence: 99%
“…Isolates E55 and 328 from Tunisia (2014) and Algeria (2013), respectively, were consistently assigned to the subgenogroup C2. Both isolates were related to strains isolated in France during the same year but were relatively distant from strains reported in Mauretania, Senegal, and Guinea ( Fernandez-Garcia et al, 2018 ) ( Figure 6C ). Isolates S14 (2011) and E30 (2014) from Tunisia were consistently assigned to the subgenogroup C4, along with isolates collected in France in 2012 ( Figure 6D ).…”
Section: Resultsmentioning
confidence: 59%
“…Other EV-A71 sequences available in sequences databanks were also selected to include representative of the different EV-A71 genogroups (A-G) ( Figure 6A). EV-A71 isolates found in sub-Saharan countries (n = 5) were assigned to the genogroup E and the subgenogroup C2 (Fernandez-Garcia et al, 2018). EV-A71 isolates found in Madagascar (n = 1) was assigned to the subgenogroup C4.…”
Section: Application Of the Real-time Rt-pcr Assay In The Surveillancmentioning
confidence: 99%